2022
DOI: 10.1021/acsomega.1c07240
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Analysis of Fast-Spreading Severe Acute Respiratory Syndrome Coronavirus 2 Variants and Their Effects on the Interaction with Human Angiotensin-Converting Enzyme 2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is evolving with mutations in the spike protein, especially in the receptor-binding domain (RBD). The failure of public health measures in some countries to contain the spread of the disease has given rise to novel viral variants with increased transmissibility. However, key questions about how quickly the variants can spread remain unclear. Herein, we performed a structural investigation using molecular dynamics simulations and determined dissociati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Our previous studies showed that the Spike VOCs have similar binding affinities to hACE2, but these are higher than that of Spike WT (de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022). Previously results have shown that substitutions K417N, S477N, T478K, E484K and N501Y cause an increase in binding affinity between RBD and hACE2 (Chen et al, 2021; de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022; de Souza et al, 2021; Tian et al, 2021). The substitutions L452R and F486V found in BA.4 and BA.5 play a key role in the decrease of neutralizing antibody recognition (Cao, Yisimayi, et al, 2022; Tuekprakhon et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our previous studies showed that the Spike VOCs have similar binding affinities to hACE2, but these are higher than that of Spike WT (de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022). Previously results have shown that substitutions K417N, S477N, T478K, E484K and N501Y cause an increase in binding affinity between RBD and hACE2 (Chen et al, 2021; de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022; de Souza et al, 2021; Tian et al, 2021). The substitutions L452R and F486V found in BA.4 and BA.5 play a key role in the decrease of neutralizing antibody recognition (Cao, Yisimayi, et al, 2022; Tuekprakhon et al, 2022).…”
Section: Introductionmentioning
confidence: 90%
“…When SARS-CoV-2 variants are compared, mutations can be found in any gene, but a higher number of mutations concentrate in the gene region that encodes the Spike protein (de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022). Spike is a homotrimer anchored in the viral membrane composed by S1 and S2 subunits, each performing a different role in the viral infection (de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022). The S1 subunit contains the N-terminal domain (NTD), the receptor binding domain (RBD) that play key roles in recognition of the hACE2, SD1 and SD2 domains (de Souza, de Freitas Amorim, Guardia, Dos Santos, Dos Santos, et al, 2022; de Souza, de Freitas Amorim, Guardia, Dos Santos, Ulrich, et al, 2022; Sironi et al, 2020; Souza et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the molecular targets, the Spike protein and the 3-chymotrypsin-like protease (3CLpro or Mpro, SARS-CoV-2 main protease) play key roles in vaccine and drug designs, respectively [14][15][16][17][18][19]. In particular, the 3CLpro cleaves 13 sites of two polyproteins, pp1a and pp1ab, which are results from translation of the genomic mRNA.…”
Section: Introductionmentioning
confidence: 99%